A meaningful life at work : the paradox of wellbeing - Bakar, Raida Abu (Emerald points., 2018)
A Meaningful Life at Work addresses a range of issues impacting experiences in the workplace and restricting personal growth in a professional setting. The authors explore employee wellbeing from a Malaysian perspective as a developing country, as well as the broader Asian and wider global context.